Correlation Between Sea‐Level Rise and Aspects of Future Tropical Cyclone Activity in CMIP6 Models. Issue 4 (11th April 2022) - Lockwood, Joseph W.; Oppenheimer, Michael; Lin, Ning; Kopp, Robert E.; Vecchi, Gabriel A.; Gori, Avantika
Abstract: Future coastal flood hazard at many locations will be impacted by both tropical cyclone (TC) change and relative sea‐level rise (SLR). Despite sea level and TC activity being influenced by common thermodynamic and dynamic climate variables, their future changes are generally considered independently. Here, we investigate correlations between SLR and TC change derived from simulations of 26 Coupled Model Intercomparison Project Phase 6 models. We first explore correlations between SLR and TC activity by inference from two large‐scale factors known to modulate TC activity: potential intensity (PI) and vertical wind shear. Under the high emissions SSP5‐8.5, SLR is strongly correlated with PI change (positively) and vertical wind shear change (negatively) over much of the western North Atlantic and North West Pacific, with global mean surface air temperature (GSAT) modulating the co‐variability. To explore the impact of the joint changes on flood hazard, we conduct climatological–hydrodynamic modeling at five sites along the US East and Gulf Coasts. Positive correlations between SLR and TC change alter flood hazard projections, particularly at Wilmington, Charleston and New Orleans. For example, if positive correlations between SLR and TC changes are ignored in estimating flood hazard at Wilmington, the average projected change to the historical 100 years storm tide event is under‐estimated by 12%. Our results suggest that flood hazard assessments that neglect the joint influence of these factors and that do not reflect the full distribution of GSAT change may not accurately represent future flood hazard. Plain Language Summary: Future coastal flood hazard at many locations will be influenced by sea level rise (SLR) and tropical cyclone (TC) activity. Due to their common dependence on the wider climate system, TC activity and SLR may increase in a joint manner with progressive warming. To explore joint variability, we first analyze correlations between SLR and future TC activity by inference from two large‐scale climate factors known to modulate TC activity. SLR is strongly correlated with the two large‐scale climate factors over much of the western North Atlantic and North West Pacific, with global mean surface air temperature (GSAT) modulating the joint changes. Using a set of synthetic TC events and a storm tide model, we find that positive correlations between SLR and TC change alter flood hazard projections, particularly at Wilmington, Charleston and New Orleans. Our results suggest that flood hazard assessments that neglect the joint influence of these factors and that do not reflect the full distribution of GSAT change may not accurately capture future flood hazard. Key Points: Relative sea‐level rise (SLR) at many locations is strongly correlated with vertical wind shear (negatively) and potential intensity (positively) Global mean surface air temperature change is found to modulate the co‐variability between SLR and tropical cyclone activity Flood hazard assessments that neglect the joint influence of these factors may not accurately represent future flood hazard